The crucible of public policy : New York courts in the progressive era - Dearstyne, Bruce W. (Bruce William), 1944- (State University of New York Press, 2022)
The Crucible of Public Policy: New York Courts in the Progressive Era relates the dramatic story of New York State courts, particularly the Court of Appeals, in deciding on the constitutionality of key state statutes in the progressive era. The Court of Appeals, second in importance only to the United States Supreme Court, made groundbreaking decisions on the constitutional validity of laws relating to privacy, personal liberty, state regulation of business, women workers' hours, compensation for on-the-job injuries, public health, and other vital areas. In the process, the Court became a crucible of sorts--a place where complex public policy issues of the day were argued and decided. These decisions set precedents that continue to influence contemporary debates. The book puts people--those who made the laws, were impacted by them, supported or opposed them in public forums, and the courts, attorneys, and judges--at the center of the story. Author Bruce W. Dearstyne presents new material previously unused by scholars, reflecting extensive research in the Court of Appeals' archival records.